Septic arthritis of left shoulder in pregnancy following minor hand injury - Agrawal, Neelam; Clemmey, Rhoughton; Al-Inizi, Shamma (Clinical Journal of Obstetrics and Gynecology, 2018)
Septic arthritis of the shoulder joint is rare and might affect around 3% of the general population [1]. A delay in diagnosis may increase morbidity and lead to bone and cartilage destruction [2]. Septic arthritis is an unusual complication of pregnancy and can progress to permanent arthropathy and disability [3]. Septic arthropathy in pregnancy requires multidisciplinary team involvement for prompt recognition and treatment to improve both maternal and fetal outcomes. High index of suspicion is vital when clinical and laboratory findings suggest septic arthritis. There are multiple predisposing factors reported previously for septic arthritis of the shoulder in pregnancy such as medical conditions, pyelonephritis and trauma. We report a 37 year old lady who presented at 26 weeks gestation with acute left shoulder pain and high temperature following minor left palm trauma. She also had left mastectomy with axillary clearance ten years earlier. She underwent arthroscopic wash out of her left shoulder joint and was covered with antibiotics with rapid improvement and recovery. We reinforce the importance of early multidisciplinary involvement when septic arthritis of the shoulder in pregnancy is suspected especially in women who have had previous mastectomy and axillary clearance which could be a predisposing factor for such a rare and serious joint condition in pregnancy.